Settlement of Sharia Economic Disputes: Efficiency of Implementation in Indonesian Religious Courts - Muhammad Irkham Firdaus; May Shinta Retnowati; M. Abdurrozaq (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This research is a critique of the efficiency of the sources of material law used in the settlement of sharia economic disputes to see how great the urgency is in creating sources of material law that are more specific and can be used as legally binding in sharia economic cases. This research uses descriptive qualitative research methods. The data collection method is done through observation, interviews, and documentation. Furthermore, data analysis was carried out using the methods of data reduction, data display, and conclusion/verification. The results of this study show that the source of material law in the settlement of sharia economic disputes is less efficient because the settlement of defaults and unlawful acts in the field of sharia economics still refers to the Civil Code (KUHPerdata). This finding confirms that there is a legal vacuum in sharia economic disputes, so dispute resolution only focuses on the agreed aspects of the contract, not on the form and practice of the contract. The implication is that the decision made by the judge does not fulfill the interpretative legal theory that adheres to the values of justice, fairness, and procedural due process. Ideally, the resolution of sharia economic disputes should still be based on Islamic law principles as the basis of the function of the Religious Courts. Practically, this research contributes to the conceptual framework of the source of material law in resolving sharia economic disputes in more effective Religious courts, as well as offering a concept of dispute resolution that follows the principles of the Islamic legal system.